Naive Bayes Method Monitoring Macro Nutrition and Soil Moisture Using Naive Bayes Method based on Internet of Things - Herwindo Rahadian; Anton Yudhana (Universitas Ahmad Dahlan, 2023)
The different land quality causes farmers not to know the exact quality of their agricultural land. Improper processing of agricultural land can result in a decrease in the quality of a land. The content of soil macronutrients consists of nitrogen (N), phospor (P), and potassium (K), these contents that usually affect plant growth. The development of an optical transducer for which is used to measure the wavelength of an object in everyday life can use led sensors as a light source and photo diodes as light detection using the TCRT5000 sensor as an infrared wave transmitter module. The use of the internet of things at this time is very useful to facilitate monitoring. The use of naÃ¯ve bayes to determine the resulting probability. the soil moisture content obtained averaged 20.63% and nitrogen content values with an average of 590, Phospor 513 and Potassium 670. The sending of data to ThingSpeak can be determined as desired. It is hoped that this research can be developed by refining the use of sensors and methods used to make it easier to apply in life.